How the chromatin landscape influences nuclear morphology - Sourabh Sengupta; Haritha Prabha; Daniel L. Levy (Frontiers in Cell and Developmental Biology, 2025)
Nuclear morphology is a defining cellular feature, differing based on cell type, tissue type, and species. In healthy cells, nuclear morphology is generally tightly regulated and maintained; however, dynamic changes in nuclear morphology are observed under certain conditions, for instance in early embryos and in some immune cells. Deviations in normal nuclear morphology are linked to numerous diseases, including most cancers and premature aging syndromes. Many regulators of nuclear morphology have been identified, encompassing both intranuclear, cytoplasmic, and extracellular factors. Of note, recent studies have converged on chromatin and chromatin-associated proteins as key determinants of nuclear morphology and dynamics. In this review we discuss how the chromatin landscape regulates nuclear morphology in both normal and diseased cellular states. Additionally, we highlight emerging technologies that promise to bridge critical gaps in our understanding of nuclear morphology, including new approaches to probe nuclear structure and the use of synthetic cells.